Navigating Uncertainty: International Accounting and Financial Reporting Amid Geopolitical Conflict - Noch, Muhamad Yamin (Advances: Jurnal Ekonomi & Bisnis, 2024)
This research investigates the intersection of geopolitical conflict and international accounting and financial reporting practices, aiming to understand the challenges faced by organizations and the adaptive strategies employed to navigate uncertainty effectively. Employing a qualitative research methodology, the study conducts a comprehensive literature review and analysis to explore the nuanced complexities within the research domain. The findings underscore multifaceted challenges posed by geopolitical tensions, particularly in corporate governance and financial market dynamics. Organizations, especially multinational corporations (MNCs), encounter heightened regulatory scrutiny, stakeholder distrust, and market volatility amidst geopolitical uncertainties. To address these challenges, organizations adopt adaptive governance structures, enhance stakeholder engagement, leverage technological innovations, and embrace collaborative initiatives to foster transparency and resilience in financial reporting practices. The study highlights the pivotal role of stakeholder engagement, technological innovations, and regulatory initiatives in promoting transparency and accountability amidst geopolitical turbulence. By bridging the gap between theory and practice, this research contributes to advancing knowledge and informing policy discussions on managing geopolitical risks in financial reporting. The findings emphasize the importance of continued research efforts to deepen understanding and address emerging challenges in navigating uncertainty amidst geopolitical conflict.